The Impact of Poverty in Shaping Human Security in India - Jane Jesiasti Anggrena; Nur Isdah Idris (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
India is currently the most populous country in the world, with an estimated population of approximately 1.46 billion people. Despite its significant economic growth in recent decades, poverty remains a major challenge affecting a large proportion of the population. Recent data indicate that nearly 50% of India's population is categorized as poor, while around 40% experience limited access to essential facilities and public services. Poverty in India is a multidimensional issue influenced by various interconnected factors, including unequal economic development, inadequate infrastructure, limited educational opportunities, and restricted access to healthcare services. This study aims to examine how poverty contributes not only to the formation of social class disparities but also to broader security and welfare concerns within Indian society. The research employs a qualitative descriptive method to analyze the relationship between poverty, social inequality, and security issues. The findings reveal that unbalanced urban growth and uneven distribution of resources have intensified disparities in education, healthcare, public facilities, and employment opportunities. These inequalities create social tensions that may increase the risk of crime, social unrest, and conflict among different groups within society. Therefore, addressing poverty and reducing socio-economic inequality are essential steps toward improving social welfare, maintaining stability, and strengthening human security in India.